2017
DOI: 10.1136/archdischild-2016-311545
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of sepsis in extremely premature infants

Abstract: Objective To identify genetic variants associated with sepsis (early and late-onset) using a genome wide association (GWA) analysis in a cohort of extremely premature infants. Study Design Previously generated GWA data from the Neonatal Research Network’s anonymized genomic database biorepository of extremely premature infants were used for this study. Sepsis was defined as culture-positive early-onset or late-onset sepsis or culture-proven meningitis. Genomic and whole genome amplified DNA was genotyped for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…These results were in agreement with a previous study of blood genome-wide expression profile in very low birthweight (VLBW) infants, demonstrating overexpression of genes involved in innate immunity and inflammation in septic patients in comparison to controls [ 76 ]. These aspects could be of major importance in the population of preterm newborns, who exhibited basal overexpression of genes related to inflammation in the gut in comparison to term newborns, as demonstrated by whole genome sequencing of stool-derived mRNA [ 77 ], and overexpressed in septic condition pathways related to IL-1 receptor kinase 2, fibroblast growth factor receptors, gap junctions, and cell division regulators [ 78 ]. Moreover, in a preterm pig model of necrotizing enterocolitis (NEC), the study of intestinal proteomics demonstrated that antibiotic treatment induced several beneficial mucosal pathways, including antioxidant ones, as CAT activity was significantly increased in comparison to untreated animals, suggesting that antibiotic treatment during NEC is associated to a more favorable redox profile, shifting towards antioxidant prevalence [ 79 ].…”
Section: Redox Status In Neonatal Sepsismentioning
confidence: 99%
“…These results were in agreement with a previous study of blood genome-wide expression profile in very low birthweight (VLBW) infants, demonstrating overexpression of genes involved in innate immunity and inflammation in septic patients in comparison to controls [ 76 ]. These aspects could be of major importance in the population of preterm newborns, who exhibited basal overexpression of genes related to inflammation in the gut in comparison to term newborns, as demonstrated by whole genome sequencing of stool-derived mRNA [ 77 ], and overexpressed in septic condition pathways related to IL-1 receptor kinase 2, fibroblast growth factor receptors, gap junctions, and cell division regulators [ 78 ]. Moreover, in a preterm pig model of necrotizing enterocolitis (NEC), the study of intestinal proteomics demonstrated that antibiotic treatment induced several beneficial mucosal pathways, including antioxidant ones, as CAT activity was significantly increased in comparison to untreated animals, suggesting that antibiotic treatment during NEC is associated to a more favorable redox profile, shifting towards antioxidant prevalence [ 79 ].…”
Section: Redox Status In Neonatal Sepsismentioning
confidence: 99%
“…It was detected that various genetic polymorphisms, including TNF-α, IL-1, IL-6, and IL- 10, were associated with a predisposition to infection and increased mortality in patients with sepsis ( 17 , 18 ). In a GWAS study in premature infants, Srinivasan et al ( 19 ) did not report any significant results for common sepsis genes, such as IL-6, TLR-2, TLR-4, etc.…”
Section: Discussionmentioning
confidence: 98%
“…The same cohort of patients and the same genotyping data used herein was used earlier in GWAS to interrogate potential genetic basis for sepsis ( 32 ), intraventricular hemorrhage ( 23 , 30 ) and bronchopulmonary dysplasia ( 33 ). While all these GWAS identified significant associations between SNPs or SNP clusters with the aforementioned neonatal morbidities, none of those were in the same region of chromosome 8 as the NECRISK region, or in regions on chromosomes 11 and 14 that we found to be associated with NEC.…”
Section: Discussionmentioning
confidence: 99%